Pareto ABC Analysis of Pharmaceutical Preparations for Diabetes Mellitus at Ngesti Waluyo Christian Hospital - Pinem, Elsa Nansari Febyola BR.; Soegiantoro, Didiek Hardiyanto; Kristariyanto, Yosua Adi (Jurnal EduHealth, 2025)
The availability of therapeutic drugs for diabetes mellitus is one of the factors that determines the success of diabetes mellitus treatment, thus inventory control management is needed that can guarantee the availability of sufficient, safe, and quality drugs. This study will evaluate the Pareto results of drugs for diabetes mellitus therapy and to evaluate the pharmaceutical inventory management system during 2022-2023 at Ngesti Waluyo Christian Hospital. The study collecting data from the pharmacy information system based of medicine name, consumption amount, and selling price. The cumulative percentage from the use value, used to determine categories ABC. The results of the study showed a decrease in category A from 6 drugs (2022) to 1 drug (2023). Pareto data in 2022 contained 6 A drugs and 3 B drugs which were mostly not included in the first line therapy in the hospital formulary, in Pareto 2023 it changed to category C. Pareto data in 2023 showed 1 A drug and 3 B drugs mostly included in the first line therapy. Management of pharmaceutical preparations is still done manually even though there is a pharmacy information system that records patient treatment, so that several drugs were found to be overstocked and during 2022-2023 there was a shortage of stock and empty supplies for some time. The conclusion is that there is an improvement in drug selection for diabetes mellitus therapy based on the hospital formulary. As shown by Pareto data in 2022, there are 9 drugs on A and B category mostly not included in the first line drugs, down to 4 drugs in 2023 almost all are first-line therapy. Drug inventory management has not been able to utilize data from the pharmacy information system so that there are still excess and shortages of stock during 2022-2023.